(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To compare the effectiveness of two invasive techniques of pain relief treatment with celiac block. Methodology: This is a randomized control trial study, carried out in the Department of Anaesthesiology, Shaikh Zayed Hospital Lahore, during a period of 1 year from January 2012 to January 2013. The data was entered in SPSS version 19 and analyzed. The student t test was applied for induction of hypotension after celiac block and Chi-square test was applied for pain with coin scale. Both male and female patients of 15->65 years of age. The study comprised of 100 patients, 50 in each group. P value <0.05 is considered as significant. Results: The mean age of patients was 55.10±12.5 in group A (bilateral group) and 53.15±11.3 years in group B (unilateral group). Fifty three patients were male and 47 patients were female in both groups. According to pain scale reported by National Institutes of Health, 13 (26%) patients had mild pain relief in group A and 12 (24%) in group B, 12 (24%) patients had moderate pain relief in group A and 13 (26%) in group B, while 25 (50%) patients had decrease in the maximum pain relief intensity in group A and also 25 (50%) in group B. Conclusion: It is concluded that maximum pain relief 50% in group A while 50% in group B. Induction of hypotension after celiac block upto 50%, there were 60% patients in group A and only 10% patients in group B.